A review of New Zealand and southeast Australian echinothurioids (Echinodermata: Echinothurioida)—excluding the subfamily Echinothuriinae—with a description of a new species of Tromikosoma - Anderson, Owen F. (Zootaxa, 2016)
An examination of a large collection of echinothurioid echinoids (excluding the subfamily Echinothuriinae Thomson) from museum collections in New Zealand and Australia has expanded the known diversity of the group in New Zealand from three species in two genera to seven species in five genera, and revealed a new species in the genus Tromikosoma Mortensen.New records for New Zealand and Australia are reported for Sperosoma obscurum Agassiz and Clark, 1907 and S. nudum Shigei, 1978 and new records for New Zealand are reported for Tromikosoma australe (Koehler, 1922) and Kamptosoma asterias (A. Agassiz, 1881). Tromikosoma rugosum sp. nov., remarkable for its unusual wrinkled appearance and exceedingly thin test, is described from deep water in the northeast of New Zealand. No evidence for the existence of Phormosoma rigidum A. Agassiz, 1881 as a species separate from P. bursarium A. Agassiz, 1881 was found, and synonymy with P. bursarium is proposed.Previous records of these echinoid species were rare, as they live mostly in deep water (>1000 m), and three species were previously known from the type material alone. Tromikosoma rugosum sp. nov. now falls into that category, but new material of the other species greatly expands both the number of known records and their geographical distribution. The majority of these new records are from the New Zealand region, with several additional records from south-east Australia.An updated key to the echinothurioids of New Zealand is provided.